Analysis of Gadget Usage Intensity, Study Discipline, and Biology Learning Outcomes Among Grade X MIPA Students at MA Wahid Hasyim Balung Jember - Zahro, Siti Hilyatus; Nasution, Nanda Eska Anugrah (META: Journal of Science and Technological Education, 2024)
The usage of devices in schools, especially for academic reason, has become more widespread as technological developments have advanced. The intensity of gadget usage is generally related to students' study discipline, which in turn impacts their academic performance. MA Wahid Hasyim Balung Jember is one such institution that lets students to utilize technology for educational reasons. This study aims to examine the profile of gadget usage intensity, study discipline, and biology learning outcomes among Grade X MIPA students at MA Wahid Hasyim Balung Jember. The research adopts a quantitative approach with a descriptive quantitative research design. This study employs survey and documentation methods. The sampling technique used is non-probability sampling in the form of total sampling, with a population and sample size of 93 students. A questionnaire was utilized to gather information regarding the intensity of gadget usage and students' study discipline based on their personal experiences. Documentation was used to collect transcript data of the biology learning outcomes of Grade X MIPA students at MA Wahid Hasyim Balung Jember. The study employed a closed questionnaire with a Likert scale. All questionnaire items used in this study were tested and proven valid and reliable. Based on the research findings, it was discovered that the average intensity of gadget usage among Grade X MIPA students at MA Wahid Hasyim Balung Jember was 40, categorized as high; the average study discipline was 63, categorized as moderate; and the average learning outcomes were 39, categorized as low.